2017
DOI: 10.13102/sociobiology.v64i1.1190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Motor Changes and Toxicity of Insecticides Fipronil and Imidacloprid in Africanized Honey Bees (Hymenoptera: Apidae)

Abstract: Honey bees are important pollinators and are essential in beekeeping. Honey bees get exposed to systemic pesticides while foraging in contaminated fields, and it is important to know the toxicity (LD50) and evaluate the impacts of bees’ exposure to these molecules. Fipronil and imidacloprid are systemic pesticides widely used in Brazil and other countries. The objective of this study was to determine the LD50 (24 hours) and evaluate motor changes in Africanized honey bee foragers exposed to lethal and subletha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Analyzes have shown that genes related to muscle function were downregulated, confirming the mobility impairment (Wu et al, 2017b). Motor alterations have also been reported in laboratory trials with sublethal doses of imidacloprid (Lunardi et al, 2017 andBovi et al, 2018).…”
Section: Imidaclopridmentioning
confidence: 69%
“…Analyzes have shown that genes related to muscle function were downregulated, confirming the mobility impairment (Wu et al, 2017b). Motor alterations have also been reported in laboratory trials with sublethal doses of imidacloprid (Lunardi et al, 2017 andBovi et al, 2018).…”
Section: Imidaclopridmentioning
confidence: 69%
“…This is close to one order of magnitude less than a conservatively reported LD 50 for a worker bee ( S1 Table ). However, a range of adverse behavioural and physiological effects for individuals are reported at and below this level of intoxication [ 1 , 28 , 29 , 30 , 36 , 37 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this level of fipronil desulfinyl is equivalent to the LD 50 for a single bee following dermal contact or direct ingestion of fipronil (see S2 Table ). To the best of our knowledge, no toxicological data have been published to date for fipronil desulfinyl, but a wide range of oral toxicity values have been cited in the literature for fipronil and its other common derivative, fipronil sulfone (see S2 Table and [ 36 , 38 , 43 , 49 – 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal health effects can translate into more dramatic effects, for example by increasing disease susceptibility [4,[7][8][9][10][11][12][13] or decreasing tolerance towards other stressors, such as land use intensification [14][15][16][17]. In addition, such pollutants are known to negatively affect learning abilities and/or lower activity levels [18][19][20][21][22][23][24], which may compromise insects even further [19,21,25].…”
Section: Introductionmentioning
confidence: 99%